Experiências Obtidas com o Programa Ensinar com Pesquisa da Pró-Reitoria de Graduação da USP na Área de Eficiência Energética - Caneppele, Fernando de Lima; Rabi, José Antonio (Revista de Graduação USP, 2017)
In the university teaching and learning will be meaningful only if they are supported by a permanent knowledge construction activity. Students can significantly learn through knowledge construction rationale. Incorporating energy efficiency issues in undergraduate curricula is important in view of not only labor market needs but also creating a culture of mitigating energy waste. This report shows some results from the project Implementation of Energy Audit Concepts at USP Campus in Pirassununga supported by Teaching with Research programs related to 2014 and 2015 calls. Student participation in the project (and in this thematic area) aimed at hands-on practicing while grasping in loco concepts related to energy and energy efficiency as developed throughout courses offered in either Biosystems or Food Engineering programs at FZEA-USP. Aforesaid project goal was successfully accomplished inasmuch as mentee (i.e. project) students have indeed deepened their knowledge about energy efficiency while undergraduate students have profited from more attractive classes on this subject as concepts became closer to their daily lives.